2D to 3D fusion of echocardiography and cardiac CT for TAVR and TAVI image guidance - Azira Binti Khalil; Amir Faisal; Khin Wee Lai; Siew Cheok Ng; Yih Miin Liew (Springer Berlin Heidelberg, 2024)
Indexed by SCOPUS